Co-Relation between Work Ability and Severity of Musculoskeletal Discomfort in Middle Aged Persons - Drashti H Trivedi; Megha S Sheth (Medsci Publications, 2018)
Introduction: Work ability is an acquired or natural capacity that enables an individual to perform a particular job or task successfully. Work ability index is a tool to record the working ability of employees. The objective of the study was to correlate work ability with severity of musculoskeletal disorders in middle aged person. Methods: A cross-sectional study was conducted on fifty subjects who were included by convenience sampling. Both males and females between 30 to 55 years of age were included, who were working and had musculoskeletal discomfort. A self-administered questionnaire concerning musculoskeletal discomfort and work ability was filled by all participants. Results: Mean work ability index was 42.6 + 4.65. Mean Cornell musculoskeletal discomfort questionnaire score was 1.26 + 115.01. Correlation between Work ability index and Cornell musculoskeletal discomfort questionnaire score was found using Spearman correlation coefficient (r= -0.721 p<0.001). Conclusion: There is a strong and statistically significant correlation between work ability and severity of musculoskeletal discomfort in middle aged persons.